Using Template Machine Technique and Encryption For Securing An Object In Digital Image - Ahmed Mohamed Hussein; Omar Muayad Abdullah (Genius Journals, 2023)
The research aims to apply template matching technology to a group of digital images in order to detect an eye object in the images, and then this object is encrypted in the resulting image depending on a set of algorithms (RSA, Hill Cipher, Elliptic Curve), where a comparison and evaluation were made. For the efficiency of these three algorithms after applying them to the template that was identified in the resulting image in order to determine the algorithm that gives the highest encryption rate and depending on the mean square error measure, the maximum signal-to-noise ratio, the structural similarity measure, and the time it takes to perform the encryption process, and the results were shown after determining The template to be processed is that the (RSA) algorithm gave the highest coding ratio at a rate of 0.0113, which is the best ratio based on the Structural Similarity Scale (SSIM) being closer to zero. The metrics MSE gives (18869.7) for the RSA and The metrics SSIM gives (0.010) for the RSA and the execution time for RSA was (0.115) and that is considered the best compared to other two algorithm. Consider the current status of research and forecast the future.
Keywords: template matching; RSA; algorithm; encryption process